Exocrine glands of Schwarziana quadripunctata (Hymenoptera, Apinae, Meliponini) - Cruz-Landim, C.; Reginato, R. D. (FapUNIFESP (SciELO), 2001)
This article describes the location, anatomy, histology and ontogeny of adult Schwarziana quadripunctata exocrine glands. These glands appear either as individualized organs (salivary gland system and Dufour gland) or as epidermis differentiation (tegumentary glands). Variations in the occurrence and degree of development among colony components with regard to their degree of maturity are also described.
Keywords: Development; Exocrine glands; Female castes; Males; animal; bee; cytology; exocrine gland; female; histology; male; Animals; Bees; Exocrine Glands; Female; Male